Testing the FMR1 promoter for mosaicism in DNA methylation among CpG sites, strands, and cells in FMR1-expressing males with fragile X syndrome - Stöger, Reinhard; Genereux, Diane P.; Hagerman, Randi J.; Hagerman, Paul J.; Tassone, Flora; Laird, Charles D. (Public Library of Science, 2011)
Variability among individuals in the severity of fragile X syndrome (FXS) is influenced by epigenetic methylation mosaicism, which may also be common in other complex disorders. The epigenetic signal of dense promoter DNA methylation is usually associated with gene silencing, as was initially reported for FMR1 alleles in individuals with FXS. A paradox arose when significant levels of FMR1 mRNA were reported for some males with FXS who had been reported to have predominately methylated alleles. We have used hairpin-bisufite PCR, validated with molecular batch-stamps and barcodes, to collect and assess double-stranded DNA methylation patterns from these previously studied males. These patterns enable us to distinguish among three possible forms of methylation mosaicism, any one of which could explain FMR1 expression in these males. Our data indicate that cryptic inter-cell mosaicism in DNA methylation can account for the presence of FMR1 mRNA in some individuals with FXS.